ANALYTICAL AND NUMERICAL METHODS TO OBTAIN CONTACT PATTERN OF CONVEXO-CONCAVE NOVIKOV GEARING - Tadeusz MARKOWSKI; Michał BATSCH (Scientific Journal of Silesian University of Technology. Series Transport)
Article presents analytical and numerical methods to obtain contact pattern of convexo-concave Novikov gearing. Two TCA (tooth contact analysis) methods were given wchich are based on equations of differential geometry. Difference between both of methods reveals in measurement of gap between the working teeth. Algorithms with their example results for presented methods were given. Moreover comparative analysis for application both of methods in Novikov gearing analysis were given.